MODERN MYTHS ABOUT THE PERUVIAN AMAZON - Arce-Rojas, Rodrigo Severo (2020)
The objective of this article is to review the validity of modern myths related to the Amazon and analyze their impact on public policies linked to the conservation of the Amazon. Based on a specialized bibliographic review, an inventory of modern myths related to the Amazon is made and then a classification is made for an analytical approach. Subsequently, a synthetic approach is made. Taking into account these results, it is discussed how these myths permeate public policies, the thinking and actions of forestry professionals and others involved with forests. As conclusions, it has been possible to recognize that there are still myths related to the Amazon regarding the indigenous people, the forests and the relations between the Amazon and Society. These modern myths are intertwined in time and can be transformed. The myths can be conceived as a system in which interrelations between society-culture-nature are verified. In spite of the dizzying advance of science, several of the myths continue in force, while science itself is immersed in its own myths and paradigms and subjectivity is part of the process of knowledge construction. In addition the myths are sustained by other modern myths of economic character that give primacy to the economic growth and the effectiveness of the markets like great regulators of social life. At the base of the validity of the myths is the disjunctive ontology between society and nature. Therefore, it is not surprising that in public policies the existence of some of these myths can still be verified. Key words: Amazon, Conservation, Myths, Culture, Nature.